Relationship Between Early and Late Nonsustained Ventricular Tachycardia and Cardiovascular Death in Patients With Acute Coronary Syndrome in the Platelet Inhibition and Patient Outcomes (PLATO) Trial. (February 2016) - Bui, An H.; Cannon, Christopher P.; Steg, Philippe Gabriel; Storey, Robert F.; Husted, Steen; Guo, Jianping; Im, KyungAh; James, Stefan K.; Michelson, Eric L.; Himmelmann, Anders; Held, Claes; Varenhorst, Christoph; et al.
Abstract : Background—: Nonsustained ventricular tachycardia (NSVT) is common after acute coronary syndrome (ACS) and a marker of increased risk of arrhythmogenic death. However, the prognostic significance of NSVT when evaluated with other contemporary risk markers and at later time points after ACS remains uncertain. Methods and Results—: In the Platelet Inhibition and Patient Outcomes (PLATO) trial, continuous ECGs were performed during the first 7 days after ACS (n=2866) and repeated for another 7 days at day 30 (n=1991). Median follow-up was 1 year. There was a time-varying interaction between NSVT and cardiovascular death such that NSVT was significantly associated with increased risk within the first 30 days after randomization (22/999 [2.2%] versus 16/1825 [0.9%]; adjusted hazard ratio, 2.84; 95% confidence interval, 1.39–5.79; P =0.004) but not after 30 days (28/929 [3.0%] versus 42/1734 [2.4%]; P =0.71). Detection of NSVT during the convalescent phase (n=428/1991; 21.5%) was also associated with an increased risk of cardiovascular death, and was most marked within the first 2 months after detection (1.9% versus 0.3%; adjusted hazard ratio, 5.48; 95% confidence interval, 1.07–28.20; P =0.01), and then decreasing over time such that the relationship was no longer significant by ≈5 months after ACS. Conclusions—: NSVT occurred frequently during the acute and convalescent phases of ACS. The risk of cardiovascular death associated with NSVT was the greatest during the first 30 days after presentation; however, patients with NSVT detected during the convalescent phase were also at a significantly increased risk of cardiovascular death that persisted for an additional several months after the index event. Clinical Trial Registration—: http://www.clinicaltrials.gov . Unique identifier: NCT00391872. Abstract : Supplemental Digital Content is available in the text.